Improving Students’s Reading Comprehension Through Group Discussion Technique - Tini Mogea (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine whether or not the group discussion technique improves students' reading comprehension. This study employs a pre-experimental design with a single group pre-test and post-test. This research was carried out at SMA Negeri 1, Ratahan Timur. This study's sample of 25 first-grade students consisted of 25 students. The data were obtained from the pre- and post-tests and given to the students. The results show that two students received a score of 4, five students received a score of 5, seven students received a score of 6, seven students received a score of 7, and four students received a score of 8. One student received a score of 6, two students received a score of 7, five students received a score of 8, and eight students received a score of 10. The students' post-test scores were higher than their pre-test scores, indicating that the group discussion technique was effective in teaching reading comprehension.